Kinetika Adsorpsi Ion Logam Cu2+ Menggunakan Tricalciumphosphate Sebagai Adsorben Dengan Variasi Kecepatan Pengadukan Dan Temperatur - Mustika Canra; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the heavy metals can pollute the waters is metal ions Cu2+. The purposes of this research are to observe the effect of stirring rate and temperature on the adsorption of metal ions Cu2+ using adsorbents tricalciumphsphate (TCP) and determine a suitable adsorption kinetics model. The procedure was begun by adding 1 gram of TCP into Cu2+ solution with a concentration of 3 ppm at stirring speed of 100 rpm, 200 rpm, and 300 rpm and a temperature of 30oC, 40oC, and 50oC. Samples were taken every 2 minutes, filtered and analyzed by atomic absorption spectrophotometer (AAS). The result demonstrated that the suitable kinetic model for adsorption of metal ions Cu2+ using TCP adsorbent is pseudosecond order kinetic model with adsorption kinetics constant value of 3,125 g/mg.min. The increased the stirring rate and temperature increase adsorption rat . Type of this adsorption is physics adsorption with activation energy value of 25,016 kJ / mol.Keywords: Adsorption kinetics model, the metal ion Cu2+, tricalciumphosphate, stirring rate and temperature.